Strategi Pemasaran Toko "Septia Tani" di Desa Talawaan Kecamatan Talawaan Kabupaten Minahasa Utara - Pratama, Rair Andhika; Porajouw, Oktavianus; Ngangi, Charles Reijnaldo (AGRI-SOSIOEKONOMI, 2023)
The purpose of this study was to analyze the marketing strategy at the Septia Tani Store in Talawaan Village, Talawaan District, North Minahasa Regency. The sample in this study was the Owner or owner of the "Septia Tani" Shop in Talawaan Village, Talawaan District, North Minahasa Regency. The sampling method is carried out by purposive sampling method or intentionally, because the "Septia Tani" Shop is relatively more advanced than other agricultural stores in Talawaan District. The analysis method used is SWOT analysis (Strength, Weakness, Opportunity, Threat). Data management is used with SWOT analysis and is processed through internal and external factors. Then carry out the preparation of the strategy using the SWOT matrix. Based on the results of the study, the marketing strategy of Toko Septia Tani is in the first quadrant. Toko Septia Tani is in a very advantageous position in maximizing business growth with a strategy of taking advantage of market opportunities and internal strength.